Transforming the Culture of Research and Innovation: The Case Study of RRI - Kumar Jain, Trilok (Journal of Advanced Research in HR and Organizational Management, 2023)
The authors discuss about the current status of research and what should be done to improve it. The authors present the case study of RRI, which has become a transformational tool for the future. RRI gives emphasis on open-source access of research findings, gender participation, science education and ethical research. The authors have reviewed the agenda and the tools of RRI. This article explores the fundamental concepts of research, innovation, and Responsible Research and Innovation (RRI) as integral components of societal progress. Research, characterized as a systematic and scientific study, contributes to new knowledge, methods, and solutions to societal problems. The article underscores the importance of ethical considerations in research, particularly in preventing the negative consequences of narrow-focused endeavors, such as the development of harmful weapons. RRI, a movement championed by the European Union, emerges as a transformative approach, prioritizing the overall well-being of society, fair practices, and transparent dissemination of research findings through open access channels. The discussion delves into science with and for Society (SWAFS), a key element of the Horizon 2020 program, aligning with RRI principles. SWAFS emphasizes institutional change, gender equality, territorial partnerships, citizen science, and building a knowledge base for societal benefit. Various tools and initiatives, including Scientix, GenPORT, ECSITE, and EUSEA, are highlighted for their roles in promoting responsible research practices, gender inclusion, and public engagement.